IT Sustainability for Business Advantage - Moore, Brian (Business Expert Press, 2013)
Ebook from IG Library ; IT Sustainability for Business Advantage speaks to modern managers in all functions as well as to IT professionals. Implementing an effective IT sustainability strategy is essential for organizations pursuing sustainability as a means of business advantage and this book shows how to do it. The critical first step is getting clear about the ends of the IT sustainability program--the mission must be to further the company's sustainability objectives and strategic intents should include: 1) Making IT operations as sustainable as possible; 2) Partnering with other functions to leverage IT in making their business processes more sustainable and to grow the business; and 3) Building a culture of sustainability within the IT organization. The next step is to implement strategies to achieve these ends and the book explores the ways and means of doing this. These include industry best practices on how to apply the processes, techniques, and technologies related to Green IT and IT for Sustainability (ITfS). They also include techniques for change management and building social capital.